Perovskite solar cell based on 1, 2PDADI interface modification and preparation method thereof

By introducing a 1,2PDADI interface modification layer into perovskite solar cells, the problem of perovskite and SnO2 interface recombination is solved, the electrical characteristics and efficiency of the film are improved, and the formation of high-quality perovskite films and high-performance solar energy are achieved. The development of batteries.

CN119136575APending Publication Date: 2024-12-13YUNNAN NORMAL UNIV

Patent Information

Application Number
CN202410918913.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The SnO2 electron transport layer in existing perovskite solar cells has oxygen vacancies and metal oxide disadvantages, resulting in non-radiative recombination of the interface between perovskite and SnO2, affecting device performance.

Method used

Using 1,2PDADI as the interface modification layer, a passivation layer is formed between the SnO2 electron transport layer and the perovskite absorbing layer by spin coating to inhibit interface carrier recombination and delay the perovskite crystallization process through coordination bonds. Promote the formation of large-sized grains.

Benefits of technology

It effectively inhibits the interface carrier recombination of perovskite and SnO2, improves the electrical characteristics of thin films, improves the efficiency and stability of perovskite solar cells, reduces the hysteresis effect, and promotes the formation of high-quality perovskite films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136575A_ABST
    Figure CN119136575A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite solar cell based on 1, 2PDADI (1, 2-propane diamine hydriodic acid) interface modification and a preparation method thereof, and belongs to the technical field of perovskite solar photovoltaics. The device structure of the cell sequentially comprises ITO conductive glass, a SnO2 electron transport layer, a 1, 2PDADI modification layer, a perovskite light absorption layer, a hole transport layer and an Ag counter electrode from bottom to top, the preparation method specifically comprises the following steps: (1) cleaning and blow-drying the ITO conductive glass; (2) spin-coating SnO2 nano dispersion liquid, and carrying out annealing treatment; (3) spin coating of a 1, 2PDADI / IPA solution is carried out, and annealing treatment is carried out; (4) spin-coating a perovskite precursor solution, and performing annealing treatment; (5) spin coating of a Spiro-OMeTAD precursor solution is carried out, and oxidation treatment is carried out; and (6) carrying out vacuum evaporation on an Ag counter electrode to obtain the 1, 2PDADI interface modified perovskite solar cell. The preparation process is simple and convenient, the cost is low, the prepared perovskite solar cell is small in hysteresis effect and high in photoelectric conversion efficiency, and a feasible thought and method are provided for commercialization of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of perovskite solar photovoltaic technology, and more specifically to a perovskite solar cell based on 1,2PDADI interface modification and a preparation method thereof. Background Art

[0002] With the continuous consumption of traditional energy and the serious environmental pollution it brings, vigorously developing new photovoltaic energy technology has become an important measure to solve energy shortages and environmental pollution.

[0003] As a new generation of photovoltaic technology, perovskite solar cells have achieved a photoelectric conversion efficiency of over 26.5% in just fifteen years since their birth. The development speed and superiority of efficiency have far exceeded other photovoltaic materials. Therefore, perovskite solar cells are a disruptive photovoltaic technology. Vigorously developing perovskite solar cells has become an effective way to solve the current energy and environmental difficulties.

[0004] Tin oxide (SnO2) has the advantages of excellent photoelectric properties, physical and chemical stability, and low-temperature preparation, making it one of the most common electron transport layers (ETL). Currently, the highest efficiency of SnO2-based PSCs has exceeded 26%.

[0005] However, SnO2ETL prepared by low-temperature solution method inevitably has a large number of oxygen vacancies (V O ); secondly, SnO2 has some of the disadvantages of metal oxides and is hydroxylated under ambient conditions. These defects form trap states near the SnO2 ETL valence band, inducing non-radiative recombination at the SnO2 / perovskite interface, thus affecting device performance.

[0006] Therefore, how to effectively suppress the interfacial carrier recombination between perovskite and SnO2ETL is an important strategy to achieve efficient and stable perovskite solar cells. Summary of the invention

[0007] In view of this, the object of the present invention is to provide a perovskite solar cell based on 1,2PDADI interface modification and a preparation method thereof to solve the deficiencies in the prior art.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] A perovskite solar cell based on 1,2PDADI interface modification, the device structure of which from bottom to top is ITO (indium tin oxide) conductive glass, SnO2 electron transport layer, 1,2PDADI (1,2-propylenediamine hydroiodic acid) modification layer, perovskite light absorption layer, hole transport layer and Ag (silver) counter electrode.

[0010] Furthermore, the thickness of the SnO2 electron transport layer is 20 to 60 nm; the thickness of the 1,2PDADI modification layer is 0.1 to 10 nm; the thickness of the perovskite light absorption layer is 400 to 900 nm; the thickness of the hole transport layer is 40 to 80 nm; and the thickness of the Ag counter electrode is 80 to 150 nm.

[0011] Furthermore, the thickness of the SnO2 electron transport layer is 25nm; the thickness of the 1,2PDADI modification layer is 5nm; the thickness of the perovskite light absorption layer is 650nm; the thickness of the hole transport layer is 60nm; and the thickness of the Ag counter electrode is 100nm.

[0012] Furthermore, the preparation method of the above-mentioned 1,2PDADI modified layer is: dissolve 1,2PDADI in IPA (isopropyl alcohol) to obtain a 1,2PDADI / IPA solution with a concentration of 0.1 to 5 mg / mL, and then spin-coat it on the SnO2 electron transport layer, annealing, and the result is obtained.

[0013] A method for preparing the above-mentioned perovskite solar cell based on 1,2PDADI interface modification specifically comprises the following steps:

[0014] (1) cleaning and drying the ITO conductive glass to obtain an ITO conductive substrate;

[0015] (2) Spin coating the SnO2 nanodispersion on the ITO conductive substrate and annealing to obtain a SnO2 electron transport layer;

[0016] (3) spin coating the 1,2PDADI / IPA solution on the SnO2 electron transport layer and annealing to obtain a 1,2PDADI modified layer;

[0017] (4) spin coating the perovskite precursor solution on the 1,2PDADI modified layer by a one-step method or a two-step method, and annealing to obtain a perovskite light absorbing layer;

[0018] (5) spin coating a Spiro-OMeTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene) precursor solution on the perovskite light absorbing layer and performing an oxidation treatment to obtain a hole transport layer;

[0019] (6) A Ag counter electrode is vacuum evaporated on the hole transport layer to obtain a perovskite solar cell based on 1,2PDADI interface modification.

[0020] Furthermore, in the above step (1), the cleaning and drying are specifically as follows: first, the ITO conductive glass is ultrasonically cleaned in deionized water, acetone and IPA in turn for 10 to 30 minutes, then rinsed with ethanol, and finally dried with nitrogen.

[0021] Furthermore, in the above step (2), the mass concentration of the SnO2 nano-dispersion liquid is 2.0% to 5.0%, and the spin coating amount is 20 to 40 μL / cm 2 The spin coating speed is 2000-4000 rpm, and the time is 20-40s; the annealing temperature is 140-160°C, and the time is 20-40min.

[0022] Furthermore, in the above step (3), the 1,2PDADI / IPA solution is obtained by dissolving 1,2PDADI in IPA, with a concentration of 0.1 to 5 mg / mL and a spin coating amount of 15 to 20 μL / cm 2 , spin coating volume is 15~20μL / cm 2 The spin coating speed is 3000-5000 rpm, and the time is 20-50 s; the annealing temperature is 50-100° C., and the time is 5-15 min.

[0023] Furthermore, in the above step (4), the one-step spin coating is specifically as follows: firstly, 1.05 mol / L of PbI2 (lead iodide) and 1 mol / L of MAI (CH3NH3I, methyl ammonium iodide salt) are dissolved in a mixed solvent of DMSO (dimethyl sulfoxide) and DMF (N,N-dimethylformamide) in a volume ratio of 1:4 to obtain a perovskite precursor solution, which is then spin-coated on the 1,2PDADI modified layer, and an anti-solvent is added dropwise, followed by annealing to obtain a perovskite light-absorbing layer; the spin coating amount of the perovskite precursor solution is 15 to 20 μL / cm 2 The speed is 3000-5000 rpm and the time is 40-60 s. The annealing temperature is 80-150 °C and the time is 10-30 min. The anti-solvent is ethyl acetate. The dripping time is 10 s after the start of spin coating and the dripping amount is 25-125 μL / cm 2 ;

[0024] The perovskite precursor solution for two-step spin coating is MAPbI3 (CH3NH3PbI3, methylamine lead iodide) perovskite precursor solution or FAPbI3 (CH(NH2)2PbI3, formamidinium lead iodide) perovskite precursor solution; the two-step spin coating is specifically as follows: firstly, spin coating PbI2 / DMSO / DMF solution, annealing, cooling, then spin coating MAI / MACl / IPA solution or FAI / MACl / IPA solution, annealing again, to obtain a perovskite light absorbing layer; in the PbI2 / DMSO / DMF solution, the concentration of PbI2 is 1.5 mol / L, and the volume ratio of DMSO to DMF is 1:9; the spin coating amount of the PbI2 / DMSO / DMF solution is 15-20 μL / cm 2, the spin coating speed is 1200-2000 rpm, and the spin coating time is 30-40 s; the annealing temperature is 60-80°C, and the time is 30-120 s; in the MAI / MACl / IPA solution or the FAI / MACl / IPA solution, the concentration of MAI or FAI (CH(NH2)2I, formamidine hydroiodide) is 0.6-0.9 mol / L, and the mass concentration of MACl (CH3NH3Cl, methyl ammonium chloride salt) is 10%-20%; the spin coating amount of the MAI / MACl / IPA solution or the FAI / MACL / IPA solution is 10-30 μL / cm 2 The spin coating speed is 1500-2000 rpm, and the spin coating time is 30-40 s; the relative humidity of the air for the second annealing treatment is 30%-40%, the temperature is 100-180° C., and the time is 10-20 min.

[0025] Further, in the above step (5), the Spiro-OMeTAD precursor solution is prepared by adding 72.3 mg of Spiro-OMeTAD powder, 28.8 μL of 4-tert-butylpyridine and 17.5 μL of 500 mg / mL Li-TFSI (lithium bis(trifluoromethanesulfonyl)imide) acetonitrile solution to each mL of chlorobenzene, and the spin coating amount is 12 to 20 μL / cm 2 The rotation speed of the spin coating is 3000-5000 rpm, and the time is 20-40 seconds; the oxidation treatment equipment is a constant temperature dryer, the relative humidity does not exceed 10%, and the time is 8-24 hours.

[0026] Furthermore, in the above step (6), the vacuum degree of vacuum evaporation is not greater than 5.0×10 -4 Pa.

[0027] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:

[0028] The applicant found that inserting a layer of passivation molecules between SnO2ETL and perovskite can effectively inhibit interfacial carrier recombination, and suitable passivation materials are conducive to inducing perovskite crystallization and promoting the formation of large-sized perovskite grains. The introduction of the 1,2PDADI interfacial passivation layer of the present invention not only passivates the surface defects of SnO2ETL but also improves the electrical properties of the film, promotes the formation of high-quality perovskite film, and finally obtains a perovskite solar cell with excellent performance, steadily improving efficiency and stability, and significantly reducing the hysteresis effect.

[0029] The present invention coats 1,2PDADI between the SnO2 electron transport layer and the perovskite light absorption layer by a spin coating method to form a passivation layer, thereby improving the interface energy level and inhibiting interface carrier recombination. At the same time, 1,2PDADI forms a coordination bond with the perovskite, delaying the perovskite crystallization process and promoting the formation of large-grain perovskite, thereby ultimately obtaining a high-quality perovskite film and a high-performance perovskite solar cell.

[0030] After the 1,2PDADI modification layer is introduced into the present invention, the electrical properties of the electron transport layer are improved, which is beneficial to enhancing the transport capacity of the electron transport layer. At the same time, the presence of the amino group promotes the growth of the perovskite film, and a high-quality perovskite film with large grains can be obtained. The surface roughness of the perovskite film is greatly reduced, and non-radiative recombination is significantly suppressed.

[0031] The preparation process of the invention is simple and low in cost. The prepared perovskite solar cell has small hysteresis effect and high photoelectric conversion efficiency, which provides a practical idea and method for the commercialization of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is an XPS peak fitting curve diagram of O1S of the SnO2 electron transport layer in the perovskite solar cell in Example 1;

[0033] Figure 2 It is the XPS peak fitting curve diagram of O1S of SnO2 electron transport layer in comparative perovskite solar cell;

[0034] Figure 3 The conductivity spectra of the SnO2 electron transport layer in the perovskite solar cell of Example 1 and the comparative example;

[0035] Figure 4 XRD diagrams of perovskite films in perovskite solar cells of Example 1 and Comparative Example;

[0036] Figure 5 is a SEM image of the perovskite film in the perovskite solar cell of Example 1;

[0037] Figure 6 is a SEM image of a perovskite film in a comparative perovskite solar cell;

[0038] Figure 7 This is a current density-voltage (JV) curve of the perovskite solar cell of Example 1 under standard sunlight;

[0039] Figure 8 This is the current density-voltage (JV) curve of the comparative perovskite solar cell under standard sunlight. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] Perovskite solar cell based on 1,2PDADI interface modification, from bottom to top, ITO conductive glass, 25nm thick SnO2 electron transport layer, 5nm thick 1,2PDADI modification layer, 650nm thick perovskite light absorption layer, 60nm thick hole transport layer and 100nm thick Ag counter electrode;

[0043] The above-mentioned method for preparing a perovskite solar cell based on 1,2PDADI interface modification specifically comprises the following steps:

[0044] (1) First, the ITO conductive glass was ultrasonically cleaned in deionized water, acetone and IPA for 18 minutes respectively, then rinsed with ethanol, and finally dried with nitrogen to obtain an ITO conductive substrate;

[0045] (2) First, SnO2 was dispersed in deionized water, ultrasonicated in a 0°C water bath for 10 min, filtered, and a SnO2 nanodispersion liquid with a mass concentration of 2.67% was obtained for later use; then, the ITO conductive substrate was treated with UV-ozone for 25 min, 90 μL of the SnO2 nanodispersion liquid was deposited on the ITO conductive substrate, spin-coated at a speed of 3000 rpm / min for 35 s, and finally transferred to a hot stage at 150°C for annealing for 30 min to obtain a SnO2 electron transport layer;

[0046] (3) First, 1,2PDADI was dissolved in IPA to obtain a 1,2PDADI / IPA solution with a concentration of 2.0 mg / mL, and then 60 μL of the 1,2PDADI / IPA solution was deposited on the SnO2 electron transport layer, spin-coated at a speed of 4000 rpm for 25 seconds, and finally transferred to a hot stage at 75°C for annealing for 8 minutes to obtain a 1,2PDADI modified layer;

[0047] (4) Dissolve 1.5 mmol of PbI2 in a mixed solution of 0.1 mL of DMSO and 0.9 mL of DMF, stir well to obtain a PbI2 / DMSO / DMF solution; mix and dissolve 90 mg of FAI and 9 mg of MACl in 1 mL of IPA, stir to dissolve, and obtain a FAI / MACl / IPA solution; first deposit 30 μL of the PbI2 / DMSO / DMF solution on the 1,2PDADI modified layer, spin coat at 1500 rpm / min for 38 s, then transfer to a hot plate at 70°C for annealing for 60 s to obtain a PbI2 film; after the substrate is cooled, deposit 70 μL of the FAI / MACl / IPA solution on the PbI2 film, spin coat at 1800 rpm / min for 30 s, and finally transfer to a hot plate at 40% humidity and 150°C for annealing for 14 min to obtain a perovskite light absorbing layer;

[0048] (5) First, add 72.3 mg of Spiro-OMeTAD powder, 28.8 μL of 4-tert-butylpyridine and 17.5 μL of 500 mg / mL Li-TFSI acetonitrile solution into 1 mL of chlorobenzene and mix to obtain a Spiro-OMeTAD precursor solution; then take 40 μL of the Spiro-OMeTAD precursor solution and deposit it on the perovskite light absorbing layer, spin coating at 4000 rpm for 35 seconds; finally, transfer it to a desiccator with a humidity of 10% and oxidize it for 16 hours to obtain a hole transport layer;

[0049] (6) Ag counter electrode was vacuum deposited on the hole transport layer with a vacuum degree of 5.0×10 -4 Pa, and the perovskite solar cell based on 1,2PDADI interface modification is obtained.

[0050] Example 2

[0051] The perovskite solar cell based on 1,2PDADI interface modification is different from Example 1 only in that the concentration of the 1,2PDADI / IPA solution is 1.0 mg / mL.

[0052] Example 3

[0053] The perovskite solar cell based on 1,2PDADI interface modification is different from Example 1 only in that the concentration of the 1,2PDADI / IPA solution is 1.5 mg / mL.

[0054] Example 4

[0055] The perovskite solar cell based on 1,2PDADI interface modification is different from Example 1 only in that the concentration of the 1,2PDADI / IPA solution is 2.5 mg / mL.

[0056] Comparative Example

[0057] The perovskite solar cell differs from Example 1 only in that it does not include a 1,2PDADI modification layer and step (3).

[0058] Performance Testing

[0059] 1. Take the perovskite solar cells prepared in the comparative example and Examples 1-4, and test their photovoltaic performance parameters such as open circuit voltage, short circuit current, fill factor and cell conversion efficiency.

[0060] The results are shown in Table 1.

[0061] Table 1 Photovoltaic performance parameters of perovskite solar cells in comparative examples and examples 1-4

[0062]

[0063] As can be seen from Table 1, the pre-deposited 1,2PDADI modification has a significant improvement on the photovoltaic performance of perovskite solar cells, especially the improvement on the open circuit voltage and fill factor.

[0064] 2. The XPS peak fitting curves of O1S of SnO2 electron transport layer in perovskite solar cells of Example 1 and Comparative Example 1 are shown as follows: Figure 1 and Figure 2 shown.

[0065] Depend on Figure 1 and Figure 2 It can be seen that after 1,2PDADI modification, the proportion of lattice oxygen increases, indicating that 1,2PDADI treatment can effectively passivate the defects of the SnO2 electron transport layer and improve the film quality of the SnO2 electron transport layer.

[0066] 3. The conductivity spectra of the SnO2 electron transport layer in the perovskite solar cell of Example 1 and Comparative Example 1 are as follows Figure 3 shown.

[0067] Depend on Figure 3 It can be seen that after 1,2PDADI modification, the conductivity of the SnO2 electron transport layer is improved and the conductive performance is enhanced.

[0068] 4. The XRD patterns of the perovskite films in the perovskite solar cells of Example 1 and Comparative Example 1 are as follows: Figure 4 shown.

[0069] Depend on Figure 4 It can be seen that after 1,2PDADI modification, the peak intensity of PbI2 in the perovskite film decreases, and the half-maximum full width of the (001) crystal plane decreases from 0.15 to 0.09, indicating that 1,2PDADI can effectively promote the crystallization of perovskite films.

[0070] 5. The SEM images of the perovskite films in the perovskite solar cells of Example 1 and Comparative Example 1 are shown in FIG. Figure 5 and Figure 6 shown.

[0071] Depend on Figure 5 It can be seen that the perovskite film in the perovskite solar cell of Example 1 is smooth and compact, the grain boundaries are gradually blurred, and the grain size is relatively large.

[0072] Depend on Figure 6 It can be seen that the surface of the perovskite film in the perovskite solar cell in Comparative Example 1 has many holes. The presence of holes will produce leakage channels, and the grain boundaries are more obvious and the grain size is smaller. These factors will affect the carrier transmission process in the perovskite, resulting in a decrease in the performance of the perovskite solar cell.

[0073] 6. The current density-voltage (JV) curves of the perovskite solar cells of Example 1 and Comparative Example 1 under standard sunlight are shown in FIG. Figure 7 and Figure 8 shown.

[0074] Depend on Figure 7 and Figure 8 It can be seen that after 1,2PDADI modification, V OC The increase from 1.107 V to 1.157 V is mainly attributed to the suppression of SnO2 / perovskite interface defects by 1,2-PDADI, which reduces non-radiative recombination losses. In addition, the J is increased due to the improvement of film quality and the enhancement of charge carrier transport and extraction. SC , with the favorable V OC and J SC , the perovskite solar cell in Example 1 achieved a PCE (cell conversion efficiency) of 23.77%.

[0075] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A perovskite solar cell based on 1,2PDADI interface modification, It is characterized in that The device structure of the perovskite solar cell is ITO conductive glass, SnO 2 Electron transport layer, 1,2PDADI modified layer, perovskite light absorbing layer, hole transport layer and Ag counter electrode.

2. A perovskite solar cell based on 1,2PDADI interface modification according to claim 1, It is characterized in that The SnO 2 The thickness of the electron transport layer is 20 to 60 nm; the thickness of the 1,2PDADI modified layer is 0.1 to 10 nm; the thickness of the perovskite light absorption layer is 400 to 900 nm; the thickness of the hole transport layer is 40 to 80 nm; and the thickness of the Ag counter electrode is 80 to 150 nm.

3. A perovskite solar cell based on 1,2PDADI interface modification according to claim 1 or 2, It is characterized in that The preparation method of the 1,2PDADI modified layer is as follows: 1,2PDADI is dissolved in IPA to obtain a 1,2PDADI / IPA solution with a concentration of 0.1 to 5 mg / mL, and then spin-coated on the SnO 2 Annealing is performed on the electron transport layer to obtain the product.

4. A method for preparing a perovskite solar cell based on 1,2PDADI interface modification as claimed in any one of claims 1 to 3, It is characterized in that The specific steps include: (1) cleaning and drying the ITO conductive glass to obtain an ITO conductive substrate; (2) SnO 2 The nano-dispersion liquid was spin-coated on the ITO conductive substrate and annealed to obtain SnO 2 Electron transport layer; (3) Spin coat the 1,2PDADI / IPA solution onto SnO 2 On the electron transport layer, annealing treatment is performed to obtain a 1,2PDADI modified layer; (4) spin coating the perovskite precursor solution on the 1,2PDADI modified layer by a one-step method or a two-step method, and annealing to obtain a perovskite light absorbing layer; (5) spin coating the Spiro-OMeTAD precursor solution on the perovskite light absorbing layer and oxidizing it to obtain a hole transport layer; (6) Vacuum evaporating an Ag counter electrode on the hole transport layer to obtain the perovskite solar cell based on 1,2PDADI interface modification.

5. A method for preparing a perovskite solar cell based on 1,2PDADI interface modification according to claim 4, It is characterized in that In step (1), the cleaning and drying are specifically as follows: first, the ITO conductive glass is ultrasonically cleaned in deionized water, acetone and IPA in sequence for 10 to 30 minutes, then rinsed with ethanol, and finally dried with nitrogen.

6. A method for preparing a perovskite solar cell based on 1,2PDADI interface modification according to claim 4, It is characterized in that In step (2), the SnO 2 The mass concentration of the nano-dispersion liquid is 2.0% to 5.0%, and the spin coating volume is 20 to 40 μL / cm 2 The spin coating speed is 2000-4000 rpm, and the time is 20-40s; the annealing temperature is 140-160°C, and the time is 20-40min.

7. A method for preparing a perovskite solar cell based on 1,2PDADI interface modification according to claim 4, It is characterized in that In step (3), the 1,2PDADI / IPA solution is obtained by dissolving 1,2PDADI in IPA, with a concentration of 0.1 to 5 mg / mL and a spin coating amount of 15 to 20 μL / cm 2 The spin coating speed is 3000-5000 rpm, and the time is 20-50s; the annealing temperature is 50-100°C, and the time is 5-15min.

8. The method for preparing a perovskite solar cell based on 1,2PDADI interface modification according to claim 4, It is characterized in that In step (4), the one-step spin coating method is specifically as follows: first, 1.05 mol / L PbI 2 and 1 mol / L MAI are dissolved in a mixed solvent of DMSO and DMF with a volume ratio of 1:4 to obtain a perovskite precursor solution, which is then spin-coated on the 1,2PDADI modified layer, and an anti-solvent is added dropwise, followed by annealing to obtain a perovskite light-absorbing layer; the spin-coating amount of the perovskite precursor solution is 15-20 μL / cm 2 The speed is 3000-5000 rpm and the time is 40-60 s; the temperature of the annealing treatment is 80-150°C and the time is 10-30 min; the anti-solvent is ethyl acetate, the dripping time is 10 s after the start of spin coating, and the dripping amount is 25-125 μL / cm 2 ; The perovskite precursor solution of the two-step spin coating is MAPbI 3 Perovskite precursor solution or FAPbI 3 Perovskite precursor solution; the two-step spin coating method is specifically as follows: first, spin-coat PbI 2 / DMSO / DMF solution, annealing, cooling, and then spin coating MAI / MACl / IPA solution or FAI / MACl / IPA solution, and annealing again to obtain a perovskite light absorbing layer; the PbI 2 / DMSO / DMF solution, PbI 2 The concentration of PbI is 1.5 mol / L, the volume ratio of DMSO to DMF is 1:9; 2 The spin coating volume of / DMSO / DMF solution is 15~20μL / cm 2 , the spin coating speed is 1200-2000rpm, and the spin coating time is 30-40s; the annealing temperature is 60-80°C, and the time is 30-120s; in the MAI / MACl / IPA solution or the FAI / MACl / IPA solution, the concentration of MAI or FAI is 0.6-0.9mol / L, and the mass concentration of MACl is 10%-20%; the spin coating amount of the MAI / MACl / IPA solution or the FAI / MACl / IPA solution is 10-30μL / cm 2 The spin coating speed is 1500-2000 rpm, and the spin coating time is 30-40 s; the relative humidity of the air for the re-annealing treatment is 30%-40%, the temperature is 100-180° C., and the time is 10-20 min.

9. The method for preparing a perovskite solar cell based on 1,2PDADI interface modification according to claim 4, It is characterized in that In step (5), the Spiro-OMeTAD precursor solution is prepared by adding 72.3 mg of Spiro-OMeTAD powder, 28.8 μL of 4-tert-butylpyridine and 17.5 μL of 500 mg / mL Li-TFSI acetonitrile solution to each 1 mL of chlorobenzene, and the spin coating amount is 12 to 20 μL / cm 2 The spin coating speed is 3000-5000rpm, and the time is 20-40s; the oxidation treatment equipment is a constant temperature dryer, the relative humidity does not exceed 10%, and the time is 8-24h.

10. The method for preparing a perovskite solar cell based on 1,2PDADI interface modification according to claim 8, It is characterized in that In step (6), the vacuum degree of the vacuum evaporation is not greater than 5.0×10 -4 Pa.

Citation Information

Patent Citations

  • Self-light-trapping perovskite solar cell and preparation method and application thereof

    CN116723713A

  • Perovskite passivation method based on low-temperature process and laminated solar cell

    CN117641952A

  • CDM interface modification-based perovskite battery and preparation method thereof

    CN117729787A

Cited By

  • Preparation method and application of perovskite thin film in perovskite solar cell

    CN121358153A

  • Method for improving stability of wide bandgap perovskite solar cell by regulating and controlling lattice strain to inhibit ion migration

    CN121692975A

  • Broadband-gap perovskite solar cell modified by bimolecular interface and preparation method of broadband-gap perovskite solar cell

    CN122028599A